Ni(OH)(2)-Fe2O3/CNOs ternary nanocomposite designed as an anode with complementary properties for high-performance li-ion battery - Dwivedi, Pravin Kumari; Muniraj, Vedi Kuyil Azhagan; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemistryselect, 2018)
Synthesis of the new ternary hybrid composite with excellent electrochemical performances for Li-ion battery is demonstrated. The ternary hybrid composite of Ni(OH)(2)-Fe2O3/Carbon Nano Onions (NFOC) is synthesized by using two-step solution phase method delivers a high reversible discharge capacity of 928 mAhg(-1) at 50 mAg(-1) and 673 mAhg(-1) at a higher current density of 1000 mAg(-1) with excellent rate performance. Additionally, it shows to have stable cycle life up to 1000 cycles with 96% capacity retention and more than 99% of coulombic efficiency. The synergetic effect between Ni(OH)(2), Fe2O3 and carbon nano onions (CNOs) as well as the unique feature of heterostructures are responsible for the improved electrochemical performance of the battery. The reversible reaction of Fe2O3 and Ni(OH)(2) with Li, maintains its long cycle life with higher reversible discharge capacity and CNOs improve the efficient electronic transfer, accommodate substantial volume expansion and maintain the structural integrity of the material during lithiation-delithiation process.
Keywords: Heterostructures; Long cycle stability; Superior rate capability; Ternary Composite; Transition metal oxides